Space-time block coded IQ-interleaved joint coding and modulation for AWGN and Rayleigh fading channels - Ng, S.X.; Hanzo, L. (The 57th IEEE Semiannual Vehicular Technology Conference, 2003. VTC 2003-Spring, 2003)
Space-time block coded (STBC) in-phase/quadrature-phase (IQ)-interleaved trellis coded modulation (TCM) and turbo TCM (TTCM) schemes are proposed, which are capable of quadrupling the achievable density order of the conventional symbol-interleaved TCM and TTCM schemes, when two transmit antennas are employed. The increased diversity order of the proposed schemes provides significant additional coding gains when communicating over non-dispersive Rayleigh fading channels, which is achieved without compromising the coding gain attainable over Gaussian channels. Bit-interleaved coded modulation (BICM) as well as iteratively decoded BICM (BICM-ID) is also incorporated into the proposed system and their performance is compared to that of TCM and TTCM.